Implementasi Pendidikan Soft Skills Dalam Membentuk Moralias Generasi Muda Di Era Globalisasi - Rachman, Evy Septiana; Sinthiya, Ida Ayu Putu Anggie (Edification Journal : Pendidikan Agama Islam, 2022)
Education in Indonesia in the capacity of formal education tends to be more oriented towards hard skill-based education, namely technical-based skills where the education is more oriented towards developing IQ (intelligence quotient), but this education is lacking in developing soft skills-based abilities contained in the EQ. (emotional intelligence), and spiritual intelligence (SQ). Along with the times, education that is only based on hard skills is no longer relevant to be used, therefore, learning must now be based on the development of soft skills (social interaction). This is important in shaping the character of the nation's children. Soft skills education is based on mentality so that the younger generation can adapt to the realities of life. The role of soft skills for the younger generation is very important because with soft skills that enable the younger generation to become individuals who are diligent, honest, not easy to give up, able to manage emotions well, innovative, creative, have a strong vision of life, are responsible, consistent and have adab as a human being who is able to humanize humans and the environment around them.